Clinical features of anti‐transcription intermediary factor 1γ (TIF1γ)‐positive dermatomyositis with internal malignancy and investigation of the involvement of TIF1γ expression in tumors in the pathogenesis of cancer‐associated dermatomyositis. Issue 12 (30th July 2020) - Motegi, Sei‐ichiro; Sekiguchi, Akiko; Ikeuchi, Hidekazu; Sakairi, Toru; Ogawa, Hiroomi; Fujii, Takaaki; Sohda, Makoto; Yajima, Toshiki; Ida, Shota; Takayasu, Yukihiro; Shimoda, Yuki; Hiromura, Keiju; et al.
Abstract: Anti‐transcription intermediary factor 1γ (anti‐TIF1γ) antibody (Ab) is significantly associated with internal malignancies in adult patients with dermatomyositis (DM). Although pathogenesis of cancer‐associated DM is unknown, TIF1γ overexpression in tumors has been considered to be critical for the development of DM. The objective of this study was to investigate clinical characteristics of patients with anti‐TIF1γ Ab‐positive DM and elucidate risk factors that are potentially associated with internal malignancy. In addition, we compared the expression of TIF1γ in tumor tissues of patients with anti‐TIF1γ Ab‐positive DM, anti‐TIF1γ Ab‐negative DM and without DM in order to investigate the pathogenesis of cancer‐associated DM. We analyzed 77 Japanese patients with DM, and found 19 patients to be positive for anti‐TIF1γ Ab. Patients with anti‐TIF1γ Ab‐positive DM were older and presented heliotrope rash and flagellate erythema more frequently than patients without anti‐TIF1γ Ab ( P < 0.05). Interstitial lung disease (ILD) and rapidly progressive ILD, as well as palmar violaceous erythema, were less frequent in patients with anti‐TIF1γ Ab than in patients without. Furthermore, internal malignancy and dysphagia were significantly more frequent in the anti‐TIF1γ Ab‐positive group ( P < 0.01). Male sex and dysphagia were significantly associated with internal malignancy in patients with anti‐TIF1γ Ab‐positive DM ( P < 0.01 and <0.05, respectively). Using immunohistochemistry, we examined the TIF1γ expression in tumors of 11 patients with cancer‐associated DM (anti‐TIF1γ Ab‐positive, nine; anti‐TIF1γ Ab‐negative, two) and 25 patients without DM. TIF1γ was highly expressed in all tumors, and there was no significant difference in TIF1γ expression between patients with and without DM. Furthermore, TIF1γ expressions in tumors were similar irrespective of the presence of anti‐TIF1γ Ab. These results suggest that anti‐TIF1γ antibody may not be simply induced by overexpression of TIF1γ in tumors in patients with DM, but that other mechanisms may exist.